Dampak Banjir Rob terhadap Perekonomian Warga Desa Loireng Kecamatan Sayung Kabupaten Demak - Diana, Zummi Asma; Saputri, Dian Eka; Arifin, Bani; Huda, Ahmad Nurul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Loireng Village is one of the villages in Sayung subdistrict that is affected by the rob disaster caused by low ground levels, rising sea levels, and loss of drainage which results in the entry of sea water into land areas, especially enter the rice field area. Rob disaster that occured in Loireng vill age very impactful to the local resident. Therefore researchers want to study the impact of rob floods on the economy of the residents of Loireng village. As for the data collection stages used comes from observation, documentation and interviews with residents whose land is affected by rob flooding. this type of research is qualitative research thats analyzing, describe a phenomenon or incedents on the object under study. The analysis results fom research is show that the impact of rob floods which resulted in the death of rice fields and converted into pond area so that it can support and improving the economy of the residents of Loireng village.